Структурно-морфологические особенности наноструктурных топокомпозитных покрытий триботехнического назначения - Konstantin Nikolaevich Poleshchenko; Dmitriy Nikolaevich Korotaev; Evgeniy Evgen'evich Tarasov (Вестник СибАДИ, 2017)
Structural-morphological features nanostructural the topokompozitnykh of coverings depending on the modes of ion-plasma processing are investigated. Classification of structural-morphological types of the coverings containing nanophases and nanocluster educations is given. On the basis of results of modeling of processes of a superficial mass transfer the reasons of formation of observed structural-morphological changes are studied. Recommendations about target application of products and constructive elements in compliance with structural-morphological type of a covering are made.